Novel piston technique versus Ilizarov technique for the repair of bone defect after lower limb infection - Jiafei Du (BMC, 2021)
Abstract Background We aimed to compare the effectiveness and complications of a novel piston technique versus the Ilizarov technique for the repair of bone defects after lower limb infection. Patients and methods We retrospectively reviewed 41 patients who had been treated at our department for lower extremity bone defects following osteomyelitis. There were 38 men and three women with a mean age of 43.41 (range, 12–69 years). The infected bone defects involved 36 tibias and five femurs. The piston technique (PT, group A) was used in 12 patients and the Ilizarov technique (IT, group B) in 29 patients. The mean follow-up period was 28.50 months (PT) and 29.90 months (IT). The modified Application of Methods of Illizarov (ASAMI) criteria was used to evaluate bone healing and functional recovery. Results Complete eradication of the infection and union of docking sites were accomplished in both groups. The mean external fixator index (EFI) was 42.32 days/cm in group A versus 58.85 days/cm in group B (p < 0.001). The bone outcomes were similar between groups A and B (p = 0.558) (excellent [9 vs. 19], good [3 vs.10]); group A showed better functional outcomes than group B (p < 0.05) (excellent [7 vs. 6], good [4 vs. 12], fair [0 vs. 10] and poor [1 vs. 1]). Pain was the most common complaint during follow-up, and group A had fewer cases of pin tract infection (1 vs. 6), adjacent joint stiffness (3 vs. 8), and delayed healing of the joint (0 vs. 3). Conclusions Satisfactory bone healing can be achieved by using both PT and IT, although PT demonstrated better functional results, lower EFI, and allowed early removal of the external fixation. We found that this novel piston technique can improve the comfort of patients, reduce the incidence of complications, and provide rapid and convenient rehabilitation.